2020
DOI: 10.1088/1361-6463/abcc91
|View full text |Cite
|
Sign up to set email alerts
|

Field emission from two-dimensional GeAs

Abstract: GeAs is a layered material of the IV-V groups that is attracting growing attention for possible applications in electronic and optoelectronic devices. In this study, exfoliated multilayer GeAs nanoflakes are structurally characterized and used as the channel of back-gate field-effect transistors. It is shown that their gate-modulated p-type conduction is decreased by exposure to light or electron beam. Moreover, the observation of a field emission (FE) current demonstrates the suitability of GeAs nanoflakes as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 59 publications
(138 reference statements)
0
9
0
Order By: Relevance
“…Due to the suitable mechanical, thermal, and electronic properties, several studies have considered 2D materials in field emission (FE) devices. [ 20–25 ] TMDs possess atomically sharp edges and localized defects that can enhance the local electric field and enable the extraction of a FE current with low turn‐on voltage. FE is a quantum mechanical phenomenon in which electrons, extracted from a conductor or a semiconductor surface under application of an intense electric field, move in vacuum from a cathode to an anode.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the suitable mechanical, thermal, and electronic properties, several studies have considered 2D materials in field emission (FE) devices. [ 20–25 ] TMDs possess atomically sharp edges and localized defects that can enhance the local electric field and enable the extraction of a FE current with low turn‐on voltage. FE is a quantum mechanical phenomenon in which electrons, extracted from a conductor or a semiconductor surface under application of an intense electric field, move in vacuum from a cathode to an anode.…”
Section: Introductionmentioning
confidence: 99%
“…5a-d also shows a peak at 179 cm −1 corresponding to GeAs mode. 30 The intensity of the GeSn peak is higher in congurations in which As is incorporated during annealing process. To explain the Raman shi in all congurations, the involved strains should be explained.…”
Section: Raman Analysesmentioning
confidence: 96%
“…Each monolayer GeAs was in turn composed of As–Ge–Ge–As and interacted with the neighboring layers via weak vdW forces. 12 The XRD pattern of GeAs (Fig. 1b) with obvious {201̄} reflections indicated that the single-crystal GeAs had grown along the (201̄) planes.…”
Section: Resultsmentioning
confidence: 99%